Severe multiorgan toxicity following low-dose copper sulfate poisoning in a patient with Psoriasis vulgaris on methotrexate: a case report - Prince Rueban Manivannan; Vishaalpalaniswamy Ramaswamy; Sakthikumar Soundarrajan (International Journal of Research in Medical Sciences, 2026)
Acute copper sulfate poisoning usually causes severe toxicity only after large ingestions. We report a man in his early 50s with psoriasis vulgaris receiving methotrexate who developed severe intravascular hemolysis, methemoglobinemia, acute hepatotoxicity, and acute kidney injury after ingesting only 1 g of copper sulfate. Serial peripheral blood smears, biochemical parameters, and clinical progression confirmed delayed multi-organ toxicity. He recovered following aggressive supportive care, forced alkaline diuresis, and withdrawal of methotrexate, without requiring dialysis. This case suggests that psoriasis-associated copper dysregulation and methotrexate-induced oxidative stress may lower the threshold for severe copper sulfate toxicity.